2017
DOI: 10.1002/ange.201611279
|View full text |Cite
|
Sign up to set email alerts
|

From Genome to Proteome to Elucidation of Reactions for All Eleven Known Lytic Transglycosylases from Pseudomonas aeruginosa

Abstract: An enzyme superfamily, the lytic transglycosylases (LTs), occupies the space between the two membranes of Gram‐negative bacteria. LTs catalyze the non‐hydrolytic cleavage of the bacterial peptidoglycan cell‐wall polymer. This reaction is central to the growth of the cell wall, for excavating the cell wall for protein insertion, and for monitoring the cell wall so as to initiate resistance responses to cell‐wall‐acting antibiotics. The nefarious Gram‐negative pathogen Pseudomonas aeruginosa encodes eleven LTs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Indeed, in vitro studies show that with few exception, the catalytic reactions of LTs overlap. 257,258 Most LTs are membrane-bound (designated as "Mlt" LTs) lipoproteins anchored to the inner leaflet of the outer membrane. At least one LT is anchored to the outer leaflet of the inner membrane (the MltG, which the reader recalls, regulates the nascent-glycan strand sizing).…”
Section: Lytic Transglycosylases: Liberation Of Cell-wall Fragmentsmentioning
confidence: 99%
“…Indeed, in vitro studies show that with few exception, the catalytic reactions of LTs overlap. 257,258 Most LTs are membrane-bound (designated as "Mlt" LTs) lipoproteins anchored to the inner leaflet of the outer membrane. At least one LT is anchored to the outer leaflet of the inner membrane (the MltG, which the reader recalls, regulates the nascent-glycan strand sizing).…”
Section: Lytic Transglycosylases: Liberation Of Cell-wall Fragmentsmentioning
confidence: 99%
“…This observation is likely due to the multiplicity of LTs, 11 are known in P. aeruginosa, with overlapping redundant activities. 27 Not all of the 11 LTs are expected to be inhibited by bulgecin A. 50 Bulgecin A potentiation of a clinical β-lactam antibiotic was visualized by microscopy.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%
“…Synthetic peptidoglycans 1 – 3 were prepared for this study by multi-step syntheses reported previously [44] , [45] , [46] .…”
Section: Methodsmentioning
confidence: 99%